XENOBIOTICS WORSEN THE COURS OF ACUTE MYOCARDIAL INFARCTION - Svitlyk, H.V. (World of Medicine and Biology, 2018)
The article is devoted to the actual problem of nowadays - the influence of occupational hazards (OH) on people organism. The task of the work was to determine acute period of ST-elevation myocardial infarction (STEMI) in patients with occupational hazards. We have examined 135 males with STEMI. 44 persons had been subjecting to prolonged exposure of occupational hazards (during at least 10 years) - contact with gasoline, diesel fuel, combustion products, pesticides, fertilizers, paints, varnishes, adhesives, metals, welding aerosols and others. It was founded that the early post-infarction period in such individuals was characterized by a higher activity of systemic inflammation (in comparison with persons whose working conditions weren’t related to occupational hazards), which correlated with the more frequent occurrence of cardiovascular events. Also there was a tendency to more frequent occurrence of sustained ventricular paroxysmal tachycardia, "new" ischemia and myocardial infarction, thrombus formation in the left ventricle. In this category of patients was founded a statistically significant occurrence of ventricular extrasystoles of high gradations (p